Review of Comprehensive Textbook of Echocardiography (Cardiovascular Journal, 2014)
Editor Navin C NandaPublished by Jaypee Brothers Medical Publishers (P) Ltd.Encyclopaedia on EchocardiographyDOI: http://dx.doi.org/10.3329/cardio.v6i2.18367Cardiovasc. j. 2014; 6(2): 189-190